Q&A - Ask Doubts and Get Answers

Clear All
Two of the zeroes of the given polynomial are . Therefore two of the factors of the given polynomial are  and     is a factor of the given polynomial. To find the other factors we divide the given polynomial with    The quotient we have obtained after performing the division is  (x+1)2 = 0 x = -1 The other two zeroes of the given polynomial are -1.

View All Answers (3)

A Aadil Khan
Find the remainder when x power 3 plus 3x power 2 plus 3x plus 1 is divided by 5 plus 2x
We know that  Volume of cuboid is =   It is given that volume  =   Now,                                                                                                                                                                                                  Therefore,one of the possible answer is possible  Length =   and  Breadth =   and  Height =    
We know that  Volume of cuboid is =   It is given that volume  =   Now,  Therefore,one of the possible answer is possible  Length =   and  Breadth =   and  Height =    
We know that  Area of rectangle is =   It is given that area  =   Now, by splitting the middle term method                                                                                       Therefore, two answers are possible  case (i) :-   Length =   and  Breadth =  case (ii) :-   Length =   and  Breadth = 
We know that  Area of rectangle is =   It is given that area  =   Now, by splitting middle term method                                                                                       Therefore, two answers are possible  case (i) :-   Length =   and  Breadth =  case (ii) :-   Length =   and  Breadth = 
Given is    We know that    If      then ,    Here,  Therefore, Therefore, value of    is  
Given is    We know that    If      then ,    Here,  Therefore, Therefore, value of    is  
We know that Now, It is given that   Therefore, Hence proved 
We know that Now, multiply and divide the R.H.S. by 2                                                                                                                                   Hence proved 
Given is   Now, we know that  Now, we can write    as    Here,  Therefore,                                                    
We know that  Now, we can write    as  Here,   Therefore,
We know that  Now, we can write    as  Here,   Therefore,
We know that Now,                                                                                             Hence proved 
We know that Now,                                                                                             Hence proved 
We can rewrite     as   We will use identity Here,   Therefore,                                                     
We can rewrite     as   We will use identity Here,   Therefore,                                                                    
We can rewrite     as   We will use identity Here,   Therefore,                                                            
We can rewrite     as   We will use identity Here,   Therefore,                                                     
We can rewrite     as   We will use identity Here,   Therefore,                                                     
Exams
Articles
Questions